2021
DOI: 10.2147/jir.s328955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiation Pneumonitis in Lung Cancer Patients Treated with HT versus IMRT and Circulating Lymphocyte Subsets as Predicting Risk Factors

Abstract: Purpose We sought to compare the symptomatic radiation pneumonitis (RP) in lung cancer patients treated with helical tomotherapy (HT) versus intensity-modulated radiotherapy (IMRT), and examine the predictive value of circulating lymphocyte subsets affecting the occurrence of RP. Patients and Methods Circulating lymphocyte subsets, clinical characteristics, dosimetric parameters and pulmonary function were collected from 130 lung cancer patients treated with HT (n = 53)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Previous studies have found clinical markers associated with RP. Zhang et al reported that the multivariate analysis of risk factors predicting grade ≥ 2, higher CD8 + T cell count was shown a risk factor associated with RP (p < 0.05) [22] . There are many considerable and novel characteristics were not enrolled in this study, such as CD4/8 + T cell count, CD4/8 + T cell ratio, B cell, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found clinical markers associated with RP. Zhang et al reported that the multivariate analysis of risk factors predicting grade ≥ 2, higher CD8 + T cell count was shown a risk factor associated with RP (p < 0.05) [22] . There are many considerable and novel characteristics were not enrolled in this study, such as CD4/8 + T cell count, CD4/8 + T cell ratio, B cell, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. revealed that Higher CD8+ T cell count after radiotherapy in lung cancer patients was associated with an increased risk of radiation pneumonitis ( 29 ). The neutrophil-lymphocyte ratio(NLR) was higher in patients who developed symptomatic radiation pneumonitis (p=0.012).The NLR is a useful biomarker for predicting symptomatic radiation pneumonitis development after RT in NSCLC patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al showed that the ratio during treatment (P=0.027), neutrophil-to-lymphocyte ratio at the end of treatment (P=0.001) were the independent predictors for symptomatic radiation pneumonitis in patients with Esophageal Cancer (28). Zhang et al revealed that Higher CD8+ T cell count after radiotherapy in lung cancer patients was associated with an increased risk of radiation pneumonitis (29). The neutrophillymphocyte ratio(NLR) was higher in patients who developed symptomatic radiation pneumonitis (p=0.012).The NLR is a useful biomarker for predicting symptomatic radiation pneumonitis development after RT in NSCLC patients (30).…”
Section: The Relationship Between Lymphopenia Induced By Radiotherapy...mentioning
confidence: 99%
“…Some studies have shown that monitoring CTCs plays an important role in the precise treatment of lung cancer. CTC detection has been reported to be used as an alternative method in patients with anaplastic lymphoma kinase (ALK) gene rearrangement in NSCLC when appropriate tissue biopsy samples could not be obtained [ 11 ]. It has also been suggested that CTCs in a liquid biopsy compensate for the fact that a tissue biopsy cannot fully reflect the heterogeneity of tumor cells and is thus more conducive to the dynamic monitoring of disease progression.…”
Section: Introductionmentioning
confidence: 99%